Contribution of a Training Action to the Development of Competencies in Higher Education: Innovación Metodológica - González Espinoza, Glenda; Paredes Olivares, Marcela (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
An experience of teacher training implemented in the context of curricular innovation, a process developed at the national level in the institutions of the Council of Rectors of Universities of Chile (CRUCH), is presented. This experience was carried out during the year 2017, with the implementation of the Training “Active Methodologies for the Development of Competencies”, of the Center for Teaching Improvement of the University of Atacama, and had as its main objective, to determine the degree of contribution to the implementation of the teaching-learning process, from the perception of teachers and managers, of the Pedagogy careers of the Faculty of Humanities and Education, of the UDA.